2011
DOI: 10.1016/j.bcp.2010.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Eriodictyol: A flavonoid antagonist of the TRPV1 receptor with antioxidant activity

Abstract: The transient potential vanilloid 1 receptor (TRPV1) is a calcium-permeable channel responsible for the transduction and modulation of acute and chronic pain signaling. As such, this receptor is a potential target for the treatment of a number of pain disorders. However, AMG517, a TRPV1 antagonist, presents several clinical limitations that include the induction of severe hyperthermia. The aim of this study was to investigate the possible interaction of the flavonoid eriodictyol with the TRPV1 receptor and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 46 publications
2
55
0
Order By: Relevance
“…Thus, the highly potent and selective TRPM3 blockers described in this study may help disentangle the on-target and off-target effects that are related to the anti-inflammatory or antioxidant properties of flavanones. Within this context, a painalleviating effect of eriodictyol, another flavanone with antioxidant properties, has been described and attributed to TRPV1 inhibition (Rossato et al, 2011). As outlined earlier, we were unable to reproduce inhibition of TRPV1, but demonstrated that eriodictyol efficiently blocks TRPM3.…”
mentioning
confidence: 57%
“…Thus, the highly potent and selective TRPM3 blockers described in this study may help disentangle the on-target and off-target effects that are related to the anti-inflammatory or antioxidant properties of flavanones. Within this context, a painalleviating effect of eriodictyol, another flavanone with antioxidant properties, has been described and attributed to TRPV1 inhibition (Rossato et al, 2011). As outlined earlier, we were unable to reproduce inhibition of TRPV1, but demonstrated that eriodictyol efficiently blocks TRPM3.…”
mentioning
confidence: 57%
“…The paw reaction test to a heat stimulus was performed as described previously (Hargreaves et al, 1988;Rossato et al, 2011). A radiant light beam from a 60-W light bulb was directed onto the right hind paw (99% of the total intensity was used).…”
Section: In Vivo Screening Of Trpv1 Antagonistsmentioning
confidence: 99%
“…The mechanical threshold was measured by using von Frey filaments in the up-anddown paradigm as described previously (Dixon, 1980;Rossato et al, 2011). First, mice were acclimated (1 h) in individual clear Plexiglas boxes (9 ϫ 7 ϫ 11 cm) on an elevated wire mesh platform to allow access to the plantar surface of the hind paws.…”
Section: In Vivo Screening Of Trpv1 Antagonistsmentioning
confidence: 99%
“…The effects of flavonoids on humans can be attributed to antioxidant, antioncogenic, anti-inflammatory, antimicrobial, anticancer, and cardiovascular actions (1,7). For example, eriodictyol plays critical roles in the pathogenesis of diabetes mellitus, can inhibit immunoglobulin E (IgE)/antigen (Ag)-induced type I hypersensitivity, and has antinociceptive and hyperthermic effects (8)(9)(10).…”
mentioning
confidence: 99%